Burkholderia cepacia: a rare cause of bacterial keratitis - Mohtar Ibrahim; Yap, Jin Yi (BMJ Publishing Group, 2018)
We describe the first clinical case of Burkholderia cepacia keratitis registered in Southeast Asia. A man in his mid-70s with underlying poorly controlled diabetes mellitus came with complaints of painful red left eye for 4 days. This was accompanied with photophobia and blurring of vision after being injured by a wooden particle while cutting grass. Slit-lamp examination showed a paracentral anterior corneal stromal infiltrates with overlying epithelial defect. Culture of the corneal smear isolated B. cepacia that was sensitive to ceftazidime, meropenem and bactrim (trimethorprim and sulfomethoxazole). Topical ceftazidime was given intensively to the patient and the infection resolved after 6 weeks of treatment.